Bacterial molecular machinery in the Martian cryosphere conditions - Muñoz-Hisado, Víctor; Ruiz-Blas, Fátima; Sobrado, Jesús Manuel; Garcia-Lopez, Eva; Martinez-Alonso, Emma; Alcázar, Alberto; Cid, Cristina (Frontiers in Microbiology, 2023)
The exploration of Mars is one of the main objectives of space missions since the red planet is considered to be, or was in the past, potentially habitable. Although the surface of Mars is now dry and arid, abundant research suggests that water covered Mars billions of years ago. Recently, the existence of liquid water in subglacial lakes has been postulated below the South pole of Mars. Until now, experiments have been carried out on the survival of microorganisms in Martian surface conditions, but it remains unknown how their adaptation mechanisms would be in the Martian cryosphere. In this work, two bacterial species (Bacillus subtilis and Curtobacterium flacumfaciens) were subjected to a simulated Martian environment during 24 hours using a planetary chamber. Afterward, the molecular machinery of both species was studied to investigate how they had been modified. Proteomes, the entire set of proteins expressed by each bacterium under Earth (named standard) conditions and Martian conditions, were compared using proteomic techniques. To establish this evaluation, both the expression levels of each protein, and the variation in their distribution within the different functional categories were considered. The results showed that these bacterial species followed a different strategy. The Bacillus subtilis resistance approach consisted of improving its stress response, membrane bioenergetics, degradation of biomolecules; and to a lesser extent, increasing its mobility and the formation of biofilms or resistance endospores. On the contrary, enduring strategy of Curtobacterium flacumfaciens comprised of strengthening the cell envelope, trying to protect cells from the extracellular environment. These results are especially important due to their implications for planetary protection, missions to Mars and sample return since contamination by microorganisms would invalidate the results of these investigations.